2022
DOI: 10.1136/bmjopen-2021-051389
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholders’ perceptions of adolescents’ sexual and reproductive health needs in Southeast Nigeria: a qualitative study

Abstract: ObjectivesThis study explored the perceptions of adult stakeholders on adolescents sexual and reproductive health (SRH) needs, variations of perceived needs by different social stratifiers and adolescent’s perceived interventions to address these needs. This will provide evidence that could be useful for policy and programme reviews for improving access and use of services in to meet the SRH needs of adolescents.DesignA qualitative cross-sectional study was conducted in Ebonyi state, Southeast, Nigeria. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…These predictors contribute greatly to adolescents’ perceived need for SRH information which could either hinder or promote adolescents’ access to or utilization of SRH information and services. Slightly similar to our findings, Okeke and colleagues revealed that the SRH need of adolescents varies based on some social stratifies such as gender, marital and schooling status [ 26 ]. Considering several factors, studies have shown that all adolescents should be empowered with the right SRH information through regular information campaigns, seminars, workshops, and conferences [ 26 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These predictors contribute greatly to adolescents’ perceived need for SRH information which could either hinder or promote adolescents’ access to or utilization of SRH information and services. Slightly similar to our findings, Okeke and colleagues revealed that the SRH need of adolescents varies based on some social stratifies such as gender, marital and schooling status [ 26 ]. Considering several factors, studies have shown that all adolescents should be empowered with the right SRH information through regular information campaigns, seminars, workshops, and conferences [ 26 , 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…Slightly similar to our findings, Okeke and colleagues revealed that the SRH need of adolescents varies based on some social stratifies such as gender, marital and schooling status [ 26 ]. Considering several factors, studies have shown that all adolescents should be empowered with the right SRH information through regular information campaigns, seminars, workshops, and conferences [ 26 , 28 ]. This will create demand for SRH information and other services among adolescents, empowering them to overcome their SRH needs [ 26 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Rationale: the implementation of the capacity-building intervention was preceded by a baseline assessment and scoping literature review, to determine the views and perceptions of healthcare providers toward adolescent clients seeking SRH services, the capacity needs of these healthcare providers in delivering SRH services to adolescents, and the potential feasible strategies for improving their views and perceptions, and addressing their capacity needs. The baseline assessment highlighted the need for targeted training and supportive supervision of both formal and informal healthcare providers 5 8 11 30–32…”
Section: Methodsmentioning
confidence: 99%
“…Despite the clear need for adolescents to access quality SRH services,5 6 the utilisation rate for SRH services, including contraceptives, remains considerably low among this age group 7–9. Although adolescents have considerable knowledge about contraceptive methods, they do not make use of these contraceptive methods in Nigeria 10–12.…”
Section: Introductionmentioning
confidence: 99%